Large Scale Solar Plants Integration in Electro-winning Copper Recuperation Process. (May 2015) - Cuevas, Felipe; Murray, Clare; Platzer, Werner; Heimsath, Anna
Abstract: In this article we study the integration of a solar plant to a copper recuperation process in Northern Chile. We analyze the integration of concentrating and non-concentrating solar energy technologies, identifying their main advantages and disadvantages. Given the energy demand of the process, solar field areas over 30.000 m 2 are studied.